2012
DOI: 10.1590/s0034-71672012000100019
|View full text |Cite
|
Sign up to set email alerts
|

Manejo de resíduos gerados na assistência domiciliar pela Estratégia de Saúde da Familia

Abstract: This study aimed to analyze the management of waste generated by home care. Data were collected through observation of care provided by professionals and users and/or caregivers. Data were recorded on a checklist developed according to the recommendations of RDC 306. The following wastes were generated: syringes (38.1%), needles (36.5%), adhesive plasters (31.7%), gauze (31.7%) and lancets (28.5%). The residues of group A were not segregated in all opportunities and group E were segregated 100% and 10.5% by pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
34

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 9 publications
2
22
0
34
Order By: Relevance
“…However, this portion was stored together with infectious waste, thus rendering it non-recyclable and increasing the quantity of infectious waste, with consequent financial and environmental burdens. There is significant production of common waste in public health services (Tramontini et al, 2009), but also issues relating to the time of its disposal, with the latter coinciding with the disposal time of infectious waste (Alves et al, 2012;Pereira et al, 2013). Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, this portion was stored together with infectious waste, thus rendering it non-recyclable and increasing the quantity of infectious waste, with consequent financial and environmental burdens. There is significant production of common waste in public health services (Tramontini et al, 2009), but also issues relating to the time of its disposal, with the latter coinciding with the disposal time of infectious waste (Alves et al, 2012;Pereira et al, 2013). Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this fact, if the waste separation is not adequately done during its production, all of the waste that is mixed with that of group A should be treated as potentially infectious and requires special procedures for its storage, collection, transportation and final disposal, thus increasing the treatment costs (14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…The results found, especially regarding the presence of piercing and cutting objects in plastic bags without any protection, revealed that the professionals working at the units under analysis did not incorporate The main causes of accidents with piercing and cutting objects containing biological material are associated to their disposal in inappropriate places (6,(16)(17) , being the proper management of HCSW a biosafety issue (14,18) . Primary health care professionals, however, consider that the risk of HIV infection in their daily practice is low (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Since people with diabetes can make several applications of insulin a day and verify capillary blood glucose, they must be instructed on the handling and disposal of waste. As it is an invasive procedure, independently of the location, there will be risks associated with health care (7) . Waste from services related to the care of human and animal health, including household waste, are characterized as Health Services Residues (RSSs) (8) .…”
Section: Introductionmentioning
confidence: 99%